TRANSFORMASI PADA CORAK KAIN SONGKET SASAK LOMBOK SEBAGAI TIPOGRAFI IDENTITAS - I NYOMAN YOGA SUMADEWA; HASBULLAH HASBULLAH (LPPMPP Institut Seni Indonesia Padangpanjang, 2021)
The Lombok's Sasak Songket cloth has a unique visual style and has spiritual and cultural values. Through this uniqueness, the problem in this paper is about how the process of transforming the Lombok's Sasak Songket pattern into a typographic identity. The aim is to describe the process of transforming the unique patterns of the Lombok's Sasak Songket cloth into a typographic identity. The method used in this design process is Design thinking, namely empathize (get an empathic understanding of the problem being solved), define (analyze observations and synthesize to determine the identified problem), ideate (generate several ideas to solve the problem), prototype (produce several quantities prototype), and test (testing the complete product using the best solution) based on Agus Sachari's transformation theory. Data collection was carried out through observation and literature study. In conclusion, through the process of transformation, the patterns of the Lombok's Songket Sasak are grouped into four typefaces. The first face consists of an uppercase letter (uppercase); The second face consists of lowercase letters (lowercase); The third face consists of numbers and the last face consists of punctuation marks.